2008
DOI: 10.1007/s10350-008-9334-0
|View full text |Cite
|
Sign up to set email alerts
|

Robotic Colorectal Surgery: First 50 Cases Experience

Abstract: Robotic laparoscopic colon surgery is feasible and safe. A longer operating time is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
182
0
6

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 200 publications
(197 citation statements)
references
References 15 publications
9
182
0
6
Order By: Relevance
“…В 2008 г. Spinoglio et al [29] изложил первый опыт выполнения 50 роботических операций на толстой кишке. В исследовании проведено сравнение 50 роботических и 161 лапароскопического вмешательства.…”
Section: применение роботической хирургии в современной колопроктологииunclassified
See 2 more Smart Citations
“…В 2008 г. Spinoglio et al [29] изложил первый опыт выполнения 50 роботических операций на толстой кишке. В исследовании проведено сравнение 50 роботических и 161 лапароскопического вмешательства.…”
Section: применение роботической хирургии в современной колопроктологииunclassified
“…Группа ученых во главе со Spinoglio [29] сравнила результаты 18 правосторонних и 10 левосторонних роботических гемиколэктомий с 50 лапароскопическими правосторонними и 73 левосторонними гемиколэктомиями. В ис-следовании также были проанализированы 19 роботических передних резекций прямой киш-ки и 3 случая других вмешательств на толстой кишке.…”
Section: роботизированные операции на ободочной кишкеunclassified
See 1 more Smart Citation
“…In comparative studies, the robotic assisted operation time was longer than conventional laparoscopic surgery. Spinoglio et al (2008) reported that the operation time was 383.8 min in robotic assisted colorectal resections (n=50) and 266.3 min in conventional laparoscopic colorectal resections (n=161). The operation time in the robotic group was significantly longer than the conventional laparoscopic group (P< 0.001).…”
Section: Operation Timementioning
confidence: 99%
“…In these analyses, there were no significant differences of short term clinical outcomes between the robotic assisted colectomy and the laparoscopic colectomy. Spinoglio et al (2008) compared the first 50 consecutive cases of robotic assisted colorectal surgery to 161 cases of laparoscopic colorectal surgery. The first day to diet was 1.04 day in the robotic group and 1.08 day in the laparoscopic group (P=0.603).…”
Section: Operation Timementioning
confidence: 99%